GLOBAL ARIDIFICATION AND THE DECLINE OF NPP: A COMMENTARY on Projected increases in global terrestrial net primary productivity loss caused by drought under climate change by Dan Cao, Jiahua Zhang, Jiaqi Han, Tian Zhang, Shanshan Yang, Jingwen Wang, Foyez Ahmed Prodhan, and Fengmei Yao. Issue 11 (28th October 2022) - Running, Steven W.
Abstract: Net primary production (NPP) is an important metric of the global carbon cycle, critical for monitoring climate stabilization and for societal economic products. Global NPP should be monitored continuously to adapt societal policy to emerging declines. Plain Language Summary: Global plant growth is being monitored to identify regions that may be in permanent decline due to changing climate. Key Points: Net primary production (NPP) is a critical global carbon cycle component Declines in NPP are important for society to respond to NPP influences climate and societal products